Puf6 primes 60S pre-ribosome nuclear export at low temperature - Stefan Gerhardy (Nature Portfolio, 2021)
Ribosome biogenesis is crucially dependent on proper rRNA folding, a process assisted by chaperones. Here the authors reveal how Puf6 promotes correct rRNA folding at low temperature, a condition where mis-paired RNA folding intermediates frequently accumulate.